The Number and Species of Migrating Wild Geese in Hortobágy - Gyüre, Péter; Juhász, Lajos; Nagy, Géza (Acta Agraria Debreceniensis, 2003)
This paper presents the total number and annual distribution of wild geese population on Puszta Hortobágy. Two migrating goose species, White-fronted Goose (Anser albifrons) and Bean Goose (Anser fabalis) contribute most to the total number of geese population. Feeding place selection of goose depend on the season. In autumn and winter, croplands largely provided food for geese. Due to selections among fields and parts of the field, sometimes relatively high grazing pressure for the whole area may be severely multiplied in some cases resulting potentially 100% shoot defoliation on the frequented sites of a wheat field.